2017
DOI: 10.1175/mwr-d-16-0460.1
|View full text |Cite
|
Sign up to set email alerts
|

The OWLeS IOP2b Lake-Effect Snowstorm: Shoreline Geometry and the Mesoscale Forcing of Precipitation

Abstract: Long-lake-axis-parallel (LLAP) lake-effect precipitation systems that form when the flow is parallel to the long axis of an elongated body of water frequently produce intense, highly localized snowfall. Conceptual models of these LLAP systems typically emphasize the role of thermally forced land breezes from the flanking shorelines, with low-level convergence and ascent centered near the lake axis. In reality, other factors such as shoreline geometry and differential surface roughness can strongly influence LL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 60 publications
5
48
0
Order By: Relevance
“…The current study, in contrast, indicates that in combination with orographic deflection, thermal effects and the orientation of the incoming flow with respect to the shoreline may have contributed to band enhancement along the elongated enhancement region, although additional sensitivity studies are needed to quantify the impact of these factors. The importance of shoreline geometry in sea-and lake-effect precipitation distributions was recently noted by Steenburgh and Campbell (2017) and Campbell and Steenburgh (2017), who documented the formation of similar airmass boundaries over and around Lake Ontario. Nagata (1991) found that both thermal gradients between the Korean Peninsula and the Sea of Japan, as well as the orography of the Korean Peninsula, similarly contribute to the formation of the JPCZ along the Eurasian coast of the Sea of Japan.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…The current study, in contrast, indicates that in combination with orographic deflection, thermal effects and the orientation of the incoming flow with respect to the shoreline may have contributed to band enhancement along the elongated enhancement region, although additional sensitivity studies are needed to quantify the impact of these factors. The importance of shoreline geometry in sea-and lake-effect precipitation distributions was recently noted by Steenburgh and Campbell (2017) and Campbell and Steenburgh (2017), who documented the formation of similar airmass boundaries over and around Lake Ontario. Nagata (1991) found that both thermal gradients between the Korean Peninsula and the Sea of Japan, as well as the orography of the Korean Peninsula, similarly contribute to the formation of the JPCZ along the Eurasian coast of the Sea of Japan.…”
Section: Discussionmentioning
confidence: 80%
“…An increased thermal gradient between land and water, together with the roughness gradient between these two surfaces, would, in the Northern Hemisphere, produce cyclonic rotation in flow that is parallel to a shoreline with land on the right and water on the left, favoring convergence along the streamwise-right shore and divergence along the streamwise-left shore of a lake or bay (e.g., Alestalo and Savijärvi 1985;Markowski and Richardson 2010). This effect has been identified, for example, in numerical simulations of a lake-effect storm over Lake Ontario (Steenburgh and Campbell 2017). In this case, the cyclonic rotation of the flow along the northeastern shoreline of the Shakotan Peninsula, which is the streamwise-right shore of Ishikari Bay, would add to convergence along the elongated enhancement region.…”
Section: Mechanisms Contributing To Convergence Along the Elongated Enhancement Regionmentioning
confidence: 98%
See 1 more Smart Citation
“…1 for examples). Next, to verify that each Lake Ontario dominant band was also a LLAP band according to previous definitions (e.g., Steiger et al 2013;Minder et al 2015;Veals and Steenburgh 2015;Welsh et al 2016;Steenburgh and Campbell 2017), it was required that 1) the band be roughly aligned with (within ;208 of) the long axis of Lake Ontario and 2) the NARR 850-hPa area-averaged wind vector be approximately parallel to the band. Bands meeting these criteria were classified as LLAP bands, and reflectivity images containing them were termed LLAP-band snapshots.…”
Section: Data and Processingmentioning
confidence: 99%
“…An important focus of recent research has been the often-dramatic enhancement of lake-effect snowfall over the Tug Hill Plateau, which lies east of Lake Ontario (e.g., Veals and Steenburgh 2015). The recent Ontario Winter Lake-effect Systems (OWLeS) field campaign from December 2013 to January 2014 (Kristovich et al 2017) has led to unprecedented insight into the structure and behavior of LLAP bands before, during, and shortly after landfall (Minder et al 2015;Campbell et al 2016;Welsh et al 2016;Bergmaier et al 2017;Campbell and Steenburgh 2017;Steenburgh and Campbell 2017). For example, new results indicate that precipitation enhancement over the Tug Hill Plateau is related, at least in part, to enhanced stratiform ascent rather than to orographic invigoration of convective updrafts (Minder et al 2015;Welsh et al 2016) and is also sensitive to the degree of organization of lake-effect bands (Campbell et al 2016).…”
Section: Introductionmentioning
confidence: 99%